Improved tear resistance by low environmental impact coupling of plasma reactive and additive treatment of a TPU/PET coated fabric. Issue 3 (June 2022) - Nuez, Lucile; Jacquot, Pierre-Baptiste; Léger, Romain; Ienny, Patrick; Perrin, Didier
An environmentally friendly approach, which consists in coupling a dielectric barrier discharge (DBD) based atmospheric plasma treatment with a coating of an aqueous phase polyurethane dispersion (PUD) containing blocked polyisocyanates, is proposed to improve the adhesion of a thermoplastic polyurethane (TPU) film onto a poly-(ethylene terephthalate) (PET) textile fabric. In this study, a screening digital design of experiment plan (DOE) was developed to determine the influence of process parameters on the adhesion between film and fabric and to evaluate the best possible adhesion value. The process parameters considered are: the dielectric barrier discharge power, the speed of the fabric undergoing the treatment, the concentration of polyisocyanates (NCO) in the PUD and the air gap. The adhesion was measured by a peeling test and further scanning electron microscope observations were carried out. Results showed that an increase of both the processing power and the NCO content in PUD, as well as the decrease in the DBD speed, had a positive effect on the adhesion. In addition, X-ray photoelectron spectroscopy and contact angle measurements demonstrated an increase in the oxygen/carbon atomic percentage ratio between the reference fabric and the treated fabric. Thus, the calibrated oxidation of the PET treated with DBD plasma treatment leads to a greater chemical and physical interaction with the TPU film, which results in better film-fabric adhesion.